(3Yjhf GdMbGFb hGjVGM GdWQGFas - (3YjSi GdSQGLs ((3GHQGgje Hf LYaQ GdeXaQj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj GWdY dfG ef eTGQb GdGQV TehSkG GeG HYO aEfg deG QCjfG CcKQ GdNdGFb eYGfjgG aj GdMjd ajg cKjQ ef GdYde GdfajS s
(3BNQgG (B:s
(3hef THW dSGfg HGdNjQ GfHSW aj GdbdhH MLJg hef YOe GdeOGQGJ YOe GdJhajb s
(3QJHI Ydi (B30 (3HGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdaQGSIs